Correlation of Adaptation to the Mental Health Status of Out-Of-Town Students - Dea Margaretha; Putri Nuryana Hulu; Remsinar Simbolon; Shinta Yuliana Hasibuan; Novita Barus (Indonesian Journal of Global Health Research, 2024)
Adaptation is a process of self-adjustment. Students' inability to adapt can cause mental health problems, especially among out-of-town students. Based on the initial survey conducted by researchers on 33 respondents, the results showed that most respondents had difficulty adapting, were disappointed with the new environment because they were far from their parents, had language and cultural differences, and had trouble finding friends with the same frequency, task demands, and different learning processes. Objective: This research aims to determine the corellation between adaptation and the mental health of first-year out-of-town students. Method: This quantitative research uses an analytical correlation design with a cross-sectional method. The sampling technique is purposive sampling. The sample consisted of 198 first-year out-of-town students. The research instrument used the SACQ (Student Adaptation to College Questionnaire) questionnaire for adaptation and the DASS (Depression Anxiety Stress Scale) as a mental health measuring tool. Researchers used univariate and bivariate analyses using the Spearman-Rho test. Results: The research shows a significant corellation between adaptation and the mental health of out-of-town students, with r = 0.488. Conclusions: Several factors, including age, gender, region, and ethnic origin, can influence the correlation between adaptation and mental health. Future researchers can develop this research by examining other variables or factors that influence student adaptation, mental health, and the coping strategies students use in their studies.